2021
DOI: 10.2490/prm.20210017
|View full text |Cite
|
Sign up to set email alerts
|

Potential Association of Circulating MicroRNA-181c and MicroRNA-484 Levels with Cardiorespiratory Fitness after Myocardial Infarction: A Pilot Study

Abstract: In the field of exercise physiology, there has been great interest in exploring circulating microRNAs (miRs) as potential biomarkers. However, it remains to be determined whether circulating miRs reflect cardiorespiratory fitness. The aim of this study was to investigate the association between circulating levels of specific miRs and cardiorespiratory fitness evaluated by cardiopulmonary exercise testing (CPET) after acute myocardial infarction (MI). Methods: Twenty patients who had had an acute MI were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Hypoxia, chronic inflammation, immunosuppression, ionizing radiation and other cellular microenvironmental factors can affect miRNA expression. For example, the pathological process of ischemic perfusion injury induces miR-484 expression in retinal ganglion cells ( 24 ), cardiac muscle ( 26 , 49 , 50 ) and brain tissue ( 25 ). Low-dose ionizing radiation exposure induces downregulation of miR-484 expression in small cell lung cancer cells ( 51 , 52 ).…”
Section: Important Characteristics Of Mir-484mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia, chronic inflammation, immunosuppression, ionizing radiation and other cellular microenvironmental factors can affect miRNA expression. For example, the pathological process of ischemic perfusion injury induces miR-484 expression in retinal ganglion cells ( 24 ), cardiac muscle ( 26 , 49 , 50 ) and brain tissue ( 25 ). Low-dose ionizing radiation exposure induces downregulation of miR-484 expression in small cell lung cancer cells ( 51 , 52 ).…”
Section: Important Characteristics Of Mir-484mentioning
confidence: 99%
“…Particularly, miR-484, which was shown to be a Foxo3a trans-activator, exerts a protective importance by directly targeting Fis1 during MI/R ( 48 ) (Table 2) . Moreover, ability to tolerate high-intensity exercise in patients recovering from AMI has a significant positive correlation with circulating miR-484 levels ( 49 ). Combining these results revealed that both MI/R process tissue and circulating miR-484 act as protective factors to slow down impaired cardiomyocyte function and accelerate the recovery process, promising to already be a powerful diagnostic or prognostic biomarker and a particularly promising drug target candidate for therapeutic applications in cardiovascular disease.…”
Section: The Role Of Mir-484 In Non-cancerous Diseasesmentioning
confidence: 99%
“…For example, plasma hsa-miR-181c levels is a predictive marker of exercise training response in heart failure patients (Gevaert et al ., 2021). Also, circulating levels of hsa-miR-181c in peripheral blood has been associated with exercise capacity and ventilatory inefficiency in acute myocardial infarction (Miyazawa et al ., 2021). Similarly, expression levels of miRNAs including hsa-miR-181a in extracellular vesicles in plasma has been correlated with aerobic fitness in young men (Guescini et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Exercise associated alterations in the levels of circulating hsa-miR-181 family miRNAs in the genome level datasets analysed, and reported in the other studies including that on extracellular vesicle (Gevaert et al ., 2021; Guescini et al ., 2015; Miyazawa et al ., 2021), together with the evidence that exercise influences the levels of one of the family members in testicular tissue in rats (Hadi et al ., 2022), call for a tempting speculation. Given previous bioinformatic evidence implicating extracellular circulating miRNAs as potential carriers of soma to germline information transfer in epigenetic inheritance (Sharma, 2014), and its subsequent experimental support (Gapp et al ., 2014; Sharma et al ., 2016; Chen et al ., 2016), the above associations of hsa-miR-181 family miRNAs in exercise seems tantalizing.…”
Section: Resultsmentioning
confidence: 99%
“…Miyazawa et al. identified that patients with high exercise capacity post‐MI showed markedly higher expression of circulating miR‐181c compared to those post‐MI patients with low exercise capacity 40 . If validated in larger patient cohorts, miR‐181c may provide prognostic value for post‐MI cardiopulmonary capacity.…”
Section: Mir‐181 In Cardiovascular Diseasementioning
confidence: 99%